Ten-year trends and differences in alcohol consumption among black and white female undergraduates - Barton, Barbara A; Bulmer, Sandra Minor; Mugno, Raymond; Misencik, Leann (Journal of Substance Use, 2019)
Background: Few studies have explored changing patterns of alcohol consumption among young females and differences based on race/ethnicity. Objective: This study examined differences in alcohol consumption between black and white undergraduate females and compared trends in three different measures of alcohol consumption over a 10-year period from 2004 to 2014. Methods: The CORE Alcohol and Drug Survey was used to collect data from female undergraduates attending a public university in the northeastern USA. Classes were randomly selected into the sample; class acceptance was 68% and student participation was 96%. The chi-square test examined differences between groups and the Cochrane Armitage Test for Trend assessed changes over time. Results: In 2014, for every measure of alcohol consumption examined, a significantly larger percentage of white females engaged in the behavior compared to black females. Trend analysis from 2004 to 2014 demonstrated a narrowing of this gap. Controlling for age, any alcohol use in past 30 days and binge drinking in the past 2 weeks increased significantly for black females 21 years or older. Any alcohol use in the past 30 days decreased significantly for white females under 21 years. Conclusion: These findings introduce many questions which should be explored through additional research.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-626-859-619-803 tex.type: [object Object]
Keywords: Alcohol; Article; Black person; Caucasian; United States; adult; alcohol; alcohol consumption; binge drinking; college females; dept.hhs; dept.mat; dept.pch; drinking trends; female; human; major clinical study; peer-reviewed; priority journal; race difference; undergraduate student

Trends in alcohol consumption among undergraduate students at a northeastern public university, 2002-2008. - Bulmer, Sandra Minor; Irfan, Syed; Mugno, Raymond; Barton, Barbara; Ackerman, Louise (Journal of American college health : J of ACH, 2010)
OBJECTIVE: This study examined alcohol consumption patterns and trends at a public university in the Northeast from 2002 to 2008., PARTICIPANTS: Stratified random sampling was used to select undergraduate students enrolled in courses during spring semesters in 2002, 2004, 2006, and 2008., METHODS: Data were collected during regularly scheduled classes for 4 measures of alcohol consumption and 5 demographic categories using the Core Alcohol and Drug Survey., RESULTS: Four groups showed significant increases in both frequency and volume of alcohol consumption-students who were female, over 21 years of age or over, living off-campus, or performing well academically. There were no decreasing trends for any demographic group. These results differ from national college health surveys, which have shown alcohol use remaining steady during this period., CONCLUSIONS: Campus-specific trend data can provide unique perspectives and guide programming efforts. These trends suggest a need for new intervention strategies on this campus.
7 citations (Crossref) [2023-10-31] Place: United States Bulmer, Sandra Minor. Department of Public Health, Southern Connecticut State University, New Haven, Connecticut 06515, USA. bulmers1@southernct.edu
Keywords: *Alcohol Drinking/ep [Epidemiology]; *Public Sector/sn [Statistics & Numerical Data]; *Students/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Alcohol Drinking; Alcohol consumption; College; Connecticut; Data Collection; Drinking; Female; Humans; Male; Public Sector; Risk-Taking; Statistics; Nonparametric; Students; Trends; United States; Universities; Young Adult; adult; article; dept.mat; dept.pch; drinking behavior; female; high risk behavior; human; information processing; male; nonparametric test; organization and management; peer-reviewed; statistics; student; university